2019
DOI: 10.1016/j.jcte.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia: The untreated metabolic dysfunction in people with type 2 diabetes in Latin America. ARETAEUS study outcomes

Abstract: ObjectiveTo assess oral antihyperglycemic agents (OAHA) and/or statin treatment initiation in patients with type 2 diabetes (T2D) and time from diagnosis to both types of treatment initiation and intensification.Research design and methodsWe reviewed 662 retrospective medical records of patients with T2D diagnosed by 31 general practitioner or specialist sites across Mexico, Argentina, and Brazil. Demographic and clinical information was abstracted from patients’ medical records and summarized using descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Percentage of therapy intensification in patients with HBA1c > 8% (addition of an oral hypoglycemic agent or dosage increase for an existing therapy or initiation of insulin treatment) [33,83] Percentage of therapy intensification in patients with HBA1c > 7% [84] Percentage of initiation of insulin treatment in patients with HBa1c > 9% [42] Average time elapsed between type 2 diabetes diagnosis and initiation of insulin treatment in patients with non-target HBa1c [42] Percentage of patients with HBa1c > 7% undergoing basal insulin treatment for 180 days and subjected to the intensification of insulin therapy [43] Difference between the percentage of outpatient visits in which sBP was higher than the target minus the percentage of outpatient visits in which a modification of anti-hypertensive treatment was implemented, either type or dose of treatment, divided by the number of eligible visits. The resulting value is multiplied by the average difference between sBP as measured in all visits and the target value of sBP [85] Percentage of patients with non-target levels of LDL cholesterol and treated with statins, divided by the total number of eligible patients [86] Time (days) elapsed before a therapeutic intervention subsequent to sub-optimal lab test results [87] Percentage of healthcare professionals who prescribe the initiation of insulin therapy to patients with type 2 diabetes and HbA1c at the recommended threshold of 7-7.9% [42] Number of patients without therapy intensification, divided by the total number of patients with HbA1c ≥ 7%, multiplied by 100 [52] Time spent with poor glycemic control (HbA1c 7%, > 7,5%, > 8%) in patients with type 2 diabetes treated with DPP-4i/SGLT-2i until the intensification of treatment with insulin/GLP-1RA [88] Percentage of patients lacking therapy intensification within 180 days from metformin failure [89] through a methodology equated with the use of outcome indicators (Table 3).…”
Section: Referencesmentioning
confidence: 99%
“…Percentage of therapy intensification in patients with HBA1c > 8% (addition of an oral hypoglycemic agent or dosage increase for an existing therapy or initiation of insulin treatment) [33,83] Percentage of therapy intensification in patients with HBA1c > 7% [84] Percentage of initiation of insulin treatment in patients with HBa1c > 9% [42] Average time elapsed between type 2 diabetes diagnosis and initiation of insulin treatment in patients with non-target HBa1c [42] Percentage of patients with HBa1c > 7% undergoing basal insulin treatment for 180 days and subjected to the intensification of insulin therapy [43] Difference between the percentage of outpatient visits in which sBP was higher than the target minus the percentage of outpatient visits in which a modification of anti-hypertensive treatment was implemented, either type or dose of treatment, divided by the number of eligible visits. The resulting value is multiplied by the average difference between sBP as measured in all visits and the target value of sBP [85] Percentage of patients with non-target levels of LDL cholesterol and treated with statins, divided by the total number of eligible patients [86] Time (days) elapsed before a therapeutic intervention subsequent to sub-optimal lab test results [87] Percentage of healthcare professionals who prescribe the initiation of insulin therapy to patients with type 2 diabetes and HbA1c at the recommended threshold of 7-7.9% [42] Number of patients without therapy intensification, divided by the total number of patients with HbA1c ≥ 7%, multiplied by 100 [52] Time spent with poor glycemic control (HbA1c 7%, > 7,5%, > 8%) in patients with type 2 diabetes treated with DPP-4i/SGLT-2i until the intensification of treatment with insulin/GLP-1RA [88] Percentage of patients lacking therapy intensification within 180 days from metformin failure [89] through a methodology equated with the use of outcome indicators (Table 3).…”
Section: Referencesmentioning
confidence: 99%
“…This rate is surprisingly high when compared with the results of other studies. The ARATEUS study evaluated the medical charts of 662 patients with T2DM and observed that in the first 2 years of follow-up, only 29% of patients were in use of statins for the management of the dyslipidemia ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, the ARETAEUS study results showed a delayed dyslipidemia treatment in a large cohort of T2DM patients, despite the presence of high LDL-cholesterol levels, either before or after the diagnosis of T2DM. Moreover, the antidiabetic treatment was not intensified when the glycemic targets were not reached [ 107 ]. The analysis of the indicators of therapeutic inertia using data from the Annals of the Associazione Medici Diabetologi , involving more than 300 diabetes centers throughout Italy, showed that between 2011 and 2018 the proportion of subjects with glycated hemoglobin >9% not treated with insulin had fallen from 40.5% to 28.2%, while there was no significant change in the ratio of subjects not treated with statins despite elevated LDL cholesterol levels (from 57.5% to 52.4%).…”
Section: Critical Issues On Dkd Management: Evidence From Real-world Settingsmentioning
confidence: 99%